Women's lived experience of compassionate midwifery: Human and professional. (June 2020) - Menage, Diane; Bailey, Elizabeth; Lees, Susan; Coad, Jane
Abstract: Objective: To develop an understanding of women's lived experience of compassionate midwifery Design: A qualitative study using the principles of Interpretive Phenomenological Analysis (IPA). Data was collected during interviews with 17 women who identified themselves as having received compassionate midwifery care. Findings: Women participants' experience of compassionate care from midwives was experienced through a sense of a midwife Being With them, Being in Relationship with them and Empowerment. Women were also aware of the way midwives were able to Balance potentially conflicting aspects of their work, in order to provide compassionate care. Two other themes which emerged through extensive analysis of the data related to how women set their experience of compassion in the context of their personal suffering and that compassion made a difference. These themes will be reported separately. Conclusion and implications for practice: The unique contribution of this study was to provide a window into the nature of women's lived experiences of compassionate midwifery and thus building, understanding around the qualities of compassionate midwifery and its impact on women. The findings are important because they challenge assumptions that compassion is ill-defined and therefore difficult to teach. On the contrary, compassionate midwifery was easily identified by women participants and had the features of an effective intervention for relieving their suffering. A dynamic model of Compassionate Midwifery in Balance has been proposed, providing a much-needed tool to inform practice, education and policy. Further research will build on this work by focussing on women in varied circumstances, environments and cultures and on understanding the lived experience of compassionate midwifery from the midwife's perspective.